Characterization of Blue Tourmaline from Madagascar for Exploring Its Color Origin - Ming Li (Advances in Condensed Matter Physics)
In the research, spectroscopic studies of tourmaline for color origin were performed by X-ray diffraction, Fourier transform infrared spectroscopy, ultraviolet-visible spectroscopy, and X-ray photoelectron spectroscopy. The research work emphasized the analysis of transition metal atoms, including their valence state and coordination number, in order to better understand the effect of transition metal cations on the color origin. The results showed that the blue color of the crystal is caused by the strong absorption at 725 nm in the red spectrum, which generates a symmetrical and wide absorption band. The absorption band at 725 nm is caused by charge transfer between Fe2+ at the Y site and Fe3+ at the Z site. Other ions in the crystal did not generate absorption lines in the visible spectral range. Besides position, its valence state and coordination number were clarified to reveal color variation and the origin of tourmaline. Most importantly, this spectroscopic analysis method makes the coloration mechanism of charge transfer that is difficult to be uncovered to be clearly revealed, which will provide an available material and chemical method to investigate the structure-property relationship for gems as well as reveal the genesis of beautiful colors.